The Mature Student's Handbook - Becker, Lucinda M., 1963- (Basingstoke : Palgrave Macmillan, 2009)
This is a practical guide allowing mature students to build on their strengths and overcome challenges. It covers areas such as lectures, seminars, reading and note-taking, presentations, writing, exams, time management, finance and careers.
Includes index.
Keywords: Adult college students -- Great Britain -- Handbooks, manuals, etc; Education, Higher -- Great Britain -- Handbooks, manuals, etc; Education